Renal cell carcinoma in a transplanted kidney: case report and literature review - Korkes, Fernando; Guidoni, Luiz Renato Montez; Bosco, Alvaro Alexandre Dias; Fernandes, Roni de Carvalho; Castro, Marília Germanos de; Fucs, Moacyr; Perez, Marjo Deninson Cardenuto (Brazilian Journal of Transplantation, 2005)
Introduction and objective: The cystic renal disease has been reported in patients with final stage of renal disease treated by dialysis or being submitted to renal transplantation. The renal tumor incidence in patients with acquired renal cystic disease submitted to hemodialysis is high. Recent reports have related renal cell carcinoma occurred in native kidneys with acquired cystic disease submitted to transplant. This paper has as purpose to describe a case of renal carcinoma in a renal graft. Method and Case report: We are reporting a case of renal cell carcinoma developed in a rejected allograft from a living related donor with acquired renal cystic disease 14 years (169 months) after transplantation, successfully treated by graft nephrectomy. Conclusions: Patients submitted to transplant have an increased incidence of malignancy, compared to the general population. Including our case, 24 de novo cases of renal neoplasms developed in renal allografts are reported, and to the best of our knowledge, this is the third reported case of renal cell carcinoma associated with acquired renal cystic disease in an allograft kidney.